Removal of chromate in aqueous solutions by termite nests and reduction chromate accumulation in Brassica chinensis L. - Wang, Ming; Wang, Nana; Zhou, Jiacang; Yuan, Jing; Jiang, Lijun; Lu, LingJia; Yan, Jiaqi; Gong, Shuxin; Zeng, Yang; Zhang, Runfeng; Zhi, Lifeng; Li, Ganghua (Frontiers in Sustainable Food Systems, 2024)
Chromate [Cr(VI)] is a highly toxic heavy metal element, representing one of the most prevalent sources of wastewater contamination. It poses a significant threat to human health and food safety.Therefore, effective treatment before discharging wastewater is of paramount importance. In this study, termite nests (Coptotermes formosanus and Odontotermes formosanus), as natural biomass materials, were used to adsorb Cr(VI) ions in wastewater as a strategy to reduce environmental pollution and minimize poisoning by Cr. Structural and morphological characterizations were performed using scanning electron microscope (SEM), Fourier Transform Infrared Spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) analyses. Batch adsorption experiments were conducted to evaluate the influence of termite nest dosage, coexisting ions, and pH. To gain further insight, detailed studies on adsorption kinetics, adsorption isotherms, and adsorption thermodynamics were undertaken. The results indicate that under acidic pH conditions, both termite nests exhibit the highest adsorption capacity for Cr(VI), with an optimal adsorbent dosage of 10 g/L. The maximum adsorption capacities of C. formosanus nest and O. formosanus nest for Cr(VI) were found to be 48.52 mg/g and 35.99 mg/g, respectively. Thermodynamic studies confirmed the spontaneous and endothermic nature of the adsorption process. In the rapeseed cultivation experiment, the growth status of Brassica chinensis L. post-adsorption treatment was markedly improved compared to the untreated group. Additionally, the concentration of Cr(VI) in the plants was significantly reduced. This demonstrates both the inhibitory effect of Cr(VI) on the growth of oilseed rape and the effectiveness of water remediation techniques.In addition, both types of termite nests can be effectively reused by 0.1 mol/L HCl. To the best of our knowledge, this is the first report of adsorption removal of Cr(VI) by C. formosanus nest and O. formosanus nest. Compared to traditional natural biomass adsorbents, termite nests exhibit a relatively higher adsorption capacity for Cr(VI). The results of this study demonstrate that subterranean termite nests can efficiently remove Cr(VI) from wastewater, offering the potential for a cost-effective and reusable bioremediation agent with the advantages of ease of operation.